Transient stability analysis of power system with six-phase converted transmission line - Mustafa, Mohd. Wazir; Ahmad, Mohd. Redzuan (2006)
Enhanced power transfer capability through a six-phase converted transmission system is becoming an area of growing interest in the power system industry. However, this conversion will have an impact on the system stability. In this paper, the transient stability of a 4-bus, 2 generators test system is investigated in time domain considering conversion of threephase double-circuit to the six-phase single-circuit transmission system. The paper presents also comparisons between critical clearing times for both three and six-phase cases. All types of fault on the middle of transmission line are simulated using PSCAD/EMTDC. From the simulation results, it has been shown that the 4-bus, 2 generators test system with six-phase single-circuit transmission has a better stability limits compare to the three-phase double-circuit transmission.